Rural household perceptions and willingness to pay for donkey farming : a case study of Blouberg Municipality, Capricorn District, Limpopo Province - Malepeng, Tshetshemi Joel (My University, 2025)
In rural households, donkeys are frequently seen as significant assets that support sustainable revenue generation and a way of life. Donkey farming is negatively perceived or viewed as a low-class or old-fashioned type of farming system compared to other livestock farming. Nonetheless, a few studies have been conducted on donkey farming, but very few have focused on perception and willingness to pay for donkey farming in Blouberg Local Municipality, Capricorn District, Limpopo province, South Africa. Furthermore, arguably, little or no research has been conducted to determine rural household's perceptions and willingness to pay for donkey farming. As a result, this study was conducted to fill the above-mentioned research gap and to attract relevant policy insinuations to increase the welfare of rural households through the application of perceptions and willingness to pay for donkey farming. The main aim of the study was to analyse rural household's perceptions and willingness to pay for donkey farming. To achieve this, the specific objectives were to profile the socio-economic characteristics of donkey farmers, determine the level of perceptions of rural households towards donkey farming contributions and determine the socio-economic factors influencing willingness to pay for donkey farming contributions towards household welfare. The simple random sampling method was used to obtain a representative sample. Using probability proportional to size, 120 rural households were drawn from three villages (Aurora, Earlydown and Oldlongsine). Face-to-face interviews using semi-structured questionnaires were used to collect data from respondents. To profile the socio-economic characteristics of donkey farmers, descriptive statistics were employed in the study. The Likert scale model was used to determine the level of perceptions of rural households towards donkey farming contributions. A binary logistic regression model was applied to determine the socio-economic factors influencing willingness to pay for donkey farming contribution towards household welfare. The results obtained from the survey showed that most respondents are over 60 years of age, with ages ranging from 18 years to 81 years. Moreover, results showed that the study area was dominated by male rural households, the household size average of the respondents was 5 members, and the household income of the respondents was social grants. Results found that respondents who were married and single had the highest numbers of over 50. The lickert scale results have shown that the perceptions of rural households towards donkey farming are strongly agreed as important to the livelihoods. Moreover, very few respondents have strongly disagreed with the perception that donkey farming is important. It was found that rural households in Blouberg's Local Municipality are willing to pay for donkey farming. Furthermore, the Binary Logistic Regression Model results showed that age, marital status, occupation, household size, religion, and culture significantly affect rural households’ willingness to pay for donkey farming. The study's recommendations are based on empirical data. They suggest that the local development plan considers the willingness of the government, community members, and various stakeholders (NGOs, research institutions, and municipalities, to mention a few) to pay for donkey contributions to household welfare. The study, therefore, recommends enhancing donkey farming at all levels, including policy and livestock programme priorities.
Thesis (M. Agricultural Management (Agricultural Extension)) -- University of Limpopo, 2025
Keywords: Rural households; Perception; Willingness to pay; The probability to sample size; Descriptive statistics; Likert scale; Binary logistic regression; Public opinion; Willingness to pay; Donkeys; Households -- Economic aspects; Prices